Comparative analysis of acelerated and conventional radiotherapy regimens in complex treatment of localy advanced breast cancer - A. G. Zolotkov; G. G. Aminov; Yu. A. Ragulin; I. A. Gulidov; A. B. Orkina (Сибирский онкологический журнал)
Results of treatment of 172 patients with locally advanced breast cancer (stage III) who received a radical course of radiotherapy as a component of comprehensive treatment are presents. In the study group A patients (n=66) received accelerated course radiotherapy (daily dose 3 Gy, given in 2 fraction 1,5 Gy with interval 5–6 hours). Total dose on the sternal and subclavian zone was 51 Gy (60 units TDF) and to the breast 60 Gy (70 units TDF). Patients of the control group (n=106) received the conventional radiotherapy (2 Gy, 5 times a week, total dose 60 Gy). Complete regression of tumors in the study group A was revealed in 25,7 % of cases, in the control group B only in 0,9 % of patients (p<0,001). Five-year overall survival with accelerated radiotherapy has increased on 18,7 % in comparison with conventional regimen (p <0,02).